Study of neutrophils isolated from peripheral blood of patients suffering from aggressive periodontitis at the cellular level: Receptors and cytoskeletal reorganization - Mukherjee, Saswati; Kundu, Debabrata (Journal of Indian Society of Periodontology, 2012)
Aggressive periodontitis (AgP) has been associated with polymorphonuclear leukocyte's (PMNL) dysfunction and periodontal pathogens possess variety of virulence factors that can impair PMNL's function. This study investigated the possible association between defective neutrophil adhesion and β(2) -integrin expression and defective neutrophil migration and actin polymerization level in the peripheral blood of neutrophils from the patients with AgP. A total of 30 individuals both male and female, age ranges between 13 - 48 years, were included in the study. Healthy controls (group I, n=10), chronic periodontitis (ChP) (group II, n=10), and AgP (group III, n=10), all without any systemic diseases and non-smokers, were recruited. Peripheral blood samples were taken and β(2) -integrin expression and actin polymerization levels were estimated by using fluorescence activated cell sorter analysis. In AgP cases, both average values (β(2) -integrin and actin level) were significantly less than that of normal subjects (<0.001). But for ChP cases, only the average value of actin level is significantly lower than that of normal subjects (<0.025). Lower β(2) -integrin expression in the AgP cases signifies lower neutrophil adhesion in AgP cases than normal, and the lower average value of actin polymerization for the AgP cases suggest lower migration capacity of neutrophils in AgP cases than normal.